2016
DOI: 10.3390/ijerph13030343
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L in the General German Population: Comparison and Evaluation of Three Yearly Cross-Section Surveys

Abstract: Health-related quality of life (HRQoL) is a key measure for evaluating health status in populations. Using the recent EQ-5D-5L for measurement, this study analyzed quality of life results and their stability over consecutive population surveys. Three cross-section surveys for representative samples of the general German population from 2012, 2013, and 2014 were evaluated using the EQ-5D-5L descriptive system and valuation by the Visual Analog Scale (VAS). Aggregated sample size reached 6074. The dimension with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 34 publications
9
34
0
Order By: Relevance
“…The VAS values in this study can also be compared with earlier and methodologically identical studies from 2012, 2013, and 2014, which show relatively high VAS means (83.3; 84.9; 84.8) [16]. The comparison with 2012 data (Figure 5) revealed that health state valuation remained quite stable.…”
Section: Discussionsupporting
confidence: 65%
“…The VAS values in this study can also be compared with earlier and methodologically identical studies from 2012, 2013, and 2014, which show relatively high VAS means (83.3; 84.9; 84.8) [16]. The comparison with 2012 data (Figure 5) revealed that health state valuation remained quite stable.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, further analyses are planned within the present data set focusing on the predictors of QL, such as lesion site (especially sites of high cosmetic importance), number of lesions and treatment types. Another important research question for the future is a thorough comparison between NMSC/AK patients with reference data from the general population and from other patient groups …”
Section: Discussionmentioning
confidence: 99%
“…Another important research question for the future is a thorough comparison between NMSC/AK patients with reference data from the general population and from other patient groups. [51][52][53][54] In conclusion, we analysed QL data from 1184 patients with NMSC and AK, which makes this study one of the largest reported PROM studies in the field of dermatology. Our results suggest that disease progression from AK to SCC is associated with a significant reduction in QL.…”
Section: Discussionmentioning
confidence: 99%
“…The EQ-5D-5L questions, including the VAS, were administered by written questionnaire. From 2012 to 2014, the surveys produced 6074 respondents; the methods and results have been presented in detail elsewhere [26]. The 2015 survey was conducted in the same way, adding another 2040 respondents and generally stable baseline results; for detail, see the study by Huber et al [27].…”
Section: Methodsmentioning
confidence: 99%